Gut redox and microbiome: charting the roadmap to T-cell regulation - Prasad, Sujata; Singh, Shilpi; Menge, Samuel; Mohapatra, Iteeshree; Kim, Stefan; Helland, Logan; Singh, Gatikrushna; Singh, Amar (Frontiers in Immunology, 2024)
The gastrointestinal (GI) tract redox environment, influenced by commensal microbiota and bacterial-derived metabolites, is crucial in shaping T-cell responses. Specifically, metabolites from gut microbiota (GM) exhibit robust anti-inflammatory effects, fostering the differentiation and regulation of CD8 + tissue-resident memory (TRM) cells, mucosalassociated invariant T (MAIT) cells, and stabilizing gut-resident Treg cells. Nitric oxide (NO), a pivotal redox mediator, emerges as a central regulator of T-cell functions and gut inflammation. NO impacts the composition of the gut microbiome, driving the differentiation of pro-inflammatory Th17 cells and exacerbating intestinal inflammation, and supports Treg expansion, showcasing its dual role in immune homeostasis. This review delves into the complex interplay between GI redox balance and GM metabolites, elucidating their profound impact on T-cell regulation. Additionally, it comprehensively emphasizes the critical role of GI redox, particularly reactive oxygen species (ROS) and NO, in shaping T-cell phenotype and functions. These insights offer valuable perspectives on disease mechanisms and potential therapeutic strategies for conditions associated with oxidative stress. Understanding the complex cross-talk between GI redox, GM metabolites, and T-cell responses provides valuable insights into potential therapeutic avenues for immune-mediated diseases, underscoring the significance of maintaining GI redox balance for optimal immune health.